BRAF and CTNNB1 gene mutations present as disseminated blue nevus-like melanoma: A case report - Xiuqiu LIN; Yang LI; Junjie LIN; Xinyan SHE; Xiaohua WANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
We report a case of disseminated blue nevus-like melanoma with BRAF and CTNNB1 gene mutations. A 34-year-old man developed generalized blue-black maculopapules and nodules, sized 3-15 mm in diameters, all over the body, including the palms, soles, mucosa of the mouth and eyes for more than six months. The skin pathology showed a large number of epithelioid cells and melanin in the dermis, and immunohistochemistry showed positive for HMB-45, Mitf, SOX-10 (partially), Melan-A (slightly), S-100 (slightly) and Ki-67(about 10%). BRAF V600E (c1799T>A) and CTNNB1 T41I (c.122C>T) mutations were detected by tissue melanoma-related gene detection. Multiple liver nodules were found by PET-CT examination. The patient was diagnosed with disseminated blue nevus-like melanoma. After two months of treatment with dabrafenib mesylate and trametinib, the skin rashes became smaller and no new lesions were observed. Now the patient was lost to follow up.